Israel : Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report, 2012)
A detailed assessment of Israel's compliance with the Basel Core Principles for effective banking supervision is presented. The Bachar reform that has been started in mid-2005 forced banks to divest most noncommercial banking activities, such as mutual funds, insurance, pension, and provident funds; the banks today focus on traditional banking business. As a result, the nonbank financial sector has grown rapidly, playing a larger role in credit markets. Financial supervision responsibilities in Israel are shared among several agencies. The Bank of Israel and specifically its Banking Supervision Department supervises banks.